2019
DOI: 10.1186/s12863-019-0714-3
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal route of the Asian house rat (Rattus tanezumi) on mainland China: insights from microsatellite and mitochondrial DNA

Abstract: BackgroundRattus tanezumi is a common commensal rat and an important host animal of bubonic plague in South China and Southeast Asia. The northward dispersal of this species in mainland China has been reported in recent decades, along with more recent intercontinental expansion. Population genetics of R. tanezumi in mainland China were studied to explain the relationship between dispersal history and the ancient and modern transportation networks of China.ResultsIn total, 502 individuals belonging to 18 popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 54 publications
5
34
2
1
Order By: Relevance
“…A negative D value indicated that there was a slight deleterious mutation in the purifying selection or separation of the R. tanezumi population, which may also be caused by population expansion [41,42]. Guo et al [21] performed Tajima's D and Fu & Li's tests on the D-loop and COI genes of 12 R. tanezumi populations and found recent demographic expansion of these populations, which was consistent with our findings. COI is a widely used DNA barcoding method that shows sufficient resolution and stability in biological species and is suitable for species identification.…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…A negative D value indicated that there was a slight deleterious mutation in the purifying selection or separation of the R. tanezumi population, which may also be caused by population expansion [41,42]. Guo et al [21] performed Tajima's D and Fu & Li's tests on the D-loop and COI genes of 12 R. tanezumi populations and found recent demographic expansion of these populations, which was consistent with our findings. COI is a widely used DNA barcoding method that shows sufficient resolution and stability in biological species and is suitable for species identification.…”
Section: Plos Onesupporting
confidence: 90%
“…tanezumi population, which may also be caused by population expansion [ 41 , 42 ]. Guo et al [ 21 ] performed Tajima’s D and Fu & Li’s tests on the D-loop and COI genes of 12 R . tanezumi populations and found recent demographic expansion of these populations, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rattus tanezumi (often called R. flavipectus in China) is widely distributed in the vast areas south of the Yangtze River, in Southern China. It is a very common rodent species in residential areas (especially the indoor habitats) in Central and Southern Yunnan [ 54 , 55 ]. Rattus norvegicus is widely distributed in the whole China, and it is also a very common rodent species in residential areas (especially the indoor habitats) in Yunnan, often co-occurring in the same areas with R. tanezumi [ 35 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%